If it's not what You are looking for type in the equation solver your own equation and let us solve it.
D( x )
3*x = 0
x+1 = 0
3*x = 0
3*x = 0
3*x = 0 // : 3
x = 0
x+1 = 0
x+1 = 0
x+1 = 0 // - 1
x = -1
x in (-oo:-1) U (-1:0) U (0:+oo)
3/(3*x)-(1/(x+1)) = 1 // - 1
3/(3*x)-(1/(x+1))-1 = 0
3/(3*x)-(x+1)^-1-1 = 0
1/x-1/(x+1)-1 = 0
(-1*x)/(x*(x+1))+(1*(x+1))/(x*(x+1))+(-1*x*(x+1))/(x*(x+1)) = 0
1*(x+1)-1*x*(x+1)-1*x = 0
1-x^2-x = 0
1-x^2-x = 0
1-x^2-x = 0
DELTA = (-1)^2-(-1*1*4)
DELTA = 5
DELTA > 0
x = (5^(1/2)+1)/(-1*2) or x = (1-5^(1/2))/(-1*2)
x = (5^(1/2)+1)/(-2) or x = (1-5^(1/2))/(-2)
(x-((5^(1/2)+1)/(-2)))*(x-((1-5^(1/2))/(-2))) = 0
((x-((5^(1/2)+1)/(-2)))*(x-((1-5^(1/2))/(-2))))/(x*(x+1)) = 0
((x-((5^(1/2)+1)/(-2)))*(x-((1-5^(1/2))/(-2))))/(x*(x+1)) = 0 // * x*(x+1)
(x-((5^(1/2)+1)/(-2)))*(x-((1-5^(1/2))/(-2))) = 0
( x-((1-5^(1/2))/(-2)) )
x-((1-5^(1/2))/(-2)) = 0 // + (1-5^(1/2))/(-2)
x = (1-5^(1/2))/(-2)
( x-((5^(1/2)+1)/(-2)) )
x-((5^(1/2)+1)/(-2)) = 0 // + (5^(1/2)+1)/(-2)
x = (5^(1/2)+1)/(-2)
x in { (1-5^(1/2))/(-2), (5^(1/2)+1)/(-2) }
| 4w=w-(w-8) | | 1785y+140p-679y= | | 1/4x-32 | | 17+4x=33 | | 4(x-8)=-2 | | 30-5y=10 | | 3(2x-7)=2(x-3) | | [2x+3]-4= | | .3[5m-6]-8= | | 26x+21=22x+59 | | 13x-34=10x-33 | | 20x-6=11x-21 | | [2w-1]11= | | t^2+3t-200=0 | | 2x-1/3=-5 | | 6/y-4y-4/3y=6 | | 25x-5=22x+10 | | 8x-1=9x-3 | | [x+3]8= | | (3y-5v+1)(2y+7)= | | X(1.5x)8=650 | | 5x^3-17x^2+4x+14=0 | | X(1.5x)=650 | | 5x^3+17x^2+4x+14=0 | | 5x^2-80x+320=0 | | 4-(3-2x)=22+3x | | (2x/3)-x=(x/15)-(8/5) | | B=b+c | | x^2+18x-360=0 | | 20x+5y=4 | | 3x-5x=15 | | 16=x/20 |